Increasing Objective Cardiometabolic Burden Associated With Attenuations in the P3b Event-Related Potential Component in Older Adults - Keage, Hannah A. D.; Feuerriegel, Daniel; Greaves, Danielle; Tregoweth, Emma; Coussens, Scott; Smith, Ashleigh E. (Frontiers in Neurology, 2020)
Cardiometabolic diseases and risk factors increase the risk of late-life cognitive impairment and dementia and have also been associated with detrimental grey and white matter changes. However, the functional brain changes associated with cardiometabolic health in late-life are unclear. We sought to characterise these functional changes by recording event-related potentials (ERPs) during a n-back working memory task (0, 1 and 2 back) in 85 adults (60% female) between 50 and 80 years of age. Due to a stratified recruitment approach, participants varied widely regarding cognitive function and cardiometabolic health. Standard and objective cut-offs for high blood glucose, waist to hip ratio (i.e. obesity), high blood cholesterol, and hypertension were employed to generate a summative score for cardiometabolic burden (none, one, or two or more above cut-off). Mixed effects modelling (covarying for age and gender) revealed no statistically significant associations between cardiometabolic burden and visual P1 and N1 component amplitudes. There was a significant effect for the P3b component: as cardiometabolic burden increased, P3b amplitude decreased. We show that cardiometabolic factors related to the development of cognitive impairment and dementia in late-life associate with brain activity, as recorded via ERPs. Findings have relevance for the monitoring of lifestyle interventions (typically targeting cardiometabolic factors) in ageing, as ERPs may provide a more sensitive measure of change than cognitive performance. Further, our results raise questions related to the findings of a broad range of ERP studies where the groups compared may differ in their cardiometabolic health status (not only in psychological symptomatology).